The Use of “Capability Approach” in the Multidimensional Measurement of Poverty in Venezuela - Villegas L., Néstor L (Revista del CLAD Reforma y Democracia, 2019)
The evolution of human rights forced us to consider new factors, other than income, to classify one person as poor. In the beginning of the 90s, the United Nations Development Program incorporated the multidimensional measurement of poverty for its annual reports. In Venezuela, the first investigations referring to non-monetary factors that influenced the quality of life began in 1995, and were suspended a few years later. Based on the initial studies conducted by the Central Bureau of Statistics and Information (currently the National Institute of Statistics), as well as other research work, a multidimensional poverty measurement model is proposed for Venezuela based on the human development and capability approach to complement the official system currently used. To this end, some valuable dimensions for the people are incorporated, such as education, health, jobs, housing, nutritional capacity, security and well-being, and that have been registered in the National Survey of Living Conditions since 2014. The developed method of multidimensional measurement of poverty demonstrates its utility in the design, execution and evaluation of public policies, by focusing on the deprivation of the Venezuelan vulnerable sectors.
Keywords: Poverty; Quality of Life; Human Development; Social Indicators; Economic Indicators; Venezuela